Prediction of Oxygen Mass Transfer Coefficients in Stirred Bioreactor with Rushton Turbine Impeller for Simulated (Non-Microbial) Medias - Rahman Al-Mayah, Ameel Mohammed; Muallah, Shatha Kadhum; Abd Al-Jabbar, Aseel (Al-Khwarizmi Engineering Journal, 2017)
Abstract The study of oxygen mass transfer was conducted in a laboratory scale 5 liter stirred bioreactor equipped with one Rushton turbine impeller. The effects of superficial gas velocity, impeller speed, power input and liquid viscosity on the oxygen mass transfer were considered. Air/ water and air/CMC systems were used as a liquid media for this study. The concentration of CMC was ranging from 0.5 to 3 w/v. The experimental results show that volumetric oxygen mass transfer coefficient increases with the increase in the superficial gas velocity and impeller speed and decreases with increasing liquid viscosity. The experimental results of kla were correlated with a mathematical correlation describing the influences of the considered factors (the overall power input and the superficial gas velocity) over the studied rages. The predicted kla values give acceptable results compared with the experimental values. The following correlations were obtained: Air/water system